Kebijakan Sawit Uni Eropa dan Tantangan bagi Diplomasi Ekonomi Indonesia - Suwarno, Windratmo (Jurnal Hubungan Internasional, 2019)
Palm oil industry in Indonesia is currently facing a major challenge which began with the European Union Parliamentary Resolution on Palm Oil and Deforestation of Rainforest. Later, the European Commission ratifying the Delegated Regulation No. C (2019) 2055 Final on High and Low ILUC Risk Criteria on Biofuels. It was accused as a form of discrimination against palm oil and contained political motives as well as business competition considering the Indonesia's palm oil products are in accordance with international regulations and sustainable development goals. Therefore, a strategy for palm oil diplomacy is needed to counter this discrimination. For this reasons, Indonesian diplomacy need to provide an explanation to stakeholders in Europen Union and to carry out a regional and multilateral economic diplomacy. This paper will use qualitative methods to describe Indonesia's economic diplomacy in facing the European Union's efforts to reduce palm oil imports.